Proceedings Eighth IEEE International Conference on Computer Vision. ICCV 2001
DOI: 10.1109/iccv.2001.937543
|View full text |Cite
|
Sign up to set email alerts
|

3D hand pose reconstruction using specialized mappings

Abstract: A system for recovering 3D hand pose from monocular color sequences is proposed. The system employs a non-linear supervised learning framework, the specialized mappings architecture (SMA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(72 citation statements)
references
References 26 publications
(21 reference statements)
0
72
0
Order By: Relevance
“…For example, our tests have shown that using a face detector [30] to bootstrap initialization, considerably boosts the performance of our system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, our tests have shown that using a face detector [30] to bootstrap initialization, considerably boosts the performance of our system.…”
Section: Resultsmentioning
confidence: 99%
“…12) or specular highlights on the background objects. Initialization and subsequent segmentation accuracy could be further improved via the use of shape and blob-based motion constraints [7], and/or domainspecific constraints like face detection [30].…”
Section: Discussionmentioning
confidence: 99%
“…Early generative models were specified manually (e.g., with joint limits and smoothness constraints), while many recent generative models have been learned from motion capture data of people performing specific actions (e.g., Choo and Fleet 2001;Herda et al 2005;Pavlović et al 1999;Sidenbladh et al 2000;Sminchisescu and Jepson 2004;Urtasun et al 2006;Wachter and Nagel 1999). Discriminative models also depend strongly on human motion capture data, based on which direct mappings from image measurements to human pose and motion are learned (Agarwal and Triggs 2006;Elgammal and Lee 2004;Rosales et al 2001;Shakhnarovich et al 2003;Sminchisescu et al 2007).…”
Section: Related Workmentioning
confidence: 99%
“…The last class is further divided to appearance-based and model-based methods. Appearance-based methods [15,16,18,20] estimate hand configurations directly from images, using a precomputed mapping from the image feature space to the hand configuration. Model-based methods [2,4,5,[10][11][12] search the solution space of the problem for the hand configuration that is most compatible to the observed hand.…”
Section: Introductionmentioning
confidence: 99%